Peran E-Commerce Dalam Pengoperasian UMKM di Masa Pandemi Covid-19 - Mela Fitri Andini; Fadiyah Sefia Nafiza; Luiz Fernando; Nugia Dwi Yunita (Universitas Pendidikan Nasional, 2021)
This study aims to determine the role of increasing the income factors in e-commerce MSME on the operation of MSMEs during the Covid-19 pandemic. The method used in this research is quantitative. In this method, researchers distribute online questionnaires to 100 more respondents who are MSME owners, especially those who usemedia e-commerce in their business operations. The results of the research conducted showed that most of the MSME actors who were respondents in this study experienced an increase in their income level which was directly proportional to the development of their business operation process as seen by the increase and development of online sales through e-commerce during the Covid-19 pandemic